Dendritic Cells as Sensors, Mediators, and Regulators of Ischemic Injury - Dai, Helong; Thomson, Angus W.; Rogers, Natasha M. (Frontiers in Immunology, 2019)
Dendritic cells (DC) are highly-specialized, bone marrow (BM)-derived antigen-processing and presenting cells crucial to the induction, integration and regulation of innate and adaptive immunity. They are stimulated by damage-associated molecular patterns (DAMPS) via pattern recognition receptors to promote inflammation and initiate immune responses. In addition to residing within the parenchyma of all organs as part of the heterogeneous mononuclear phagocyte system, DC are an abundant component of the inflammatory cell infiltrate that appears in response to ischemia reperfusion injury (IRI). They can play disparate roles in the pathogenesis of IRI, since their selective depletion has been found to be protective, deleterious, or of no benefit in mouse models of IRI. In addition, administration of DC generated and manipulated ex vivo can protect organs from IRI by suppressing inflammatory cytokine production, limiting the capacity of DC to activate NKT cells, or enhancing regulatory T cell function. Few studies however have investigated specific signal transduction mechanisms underlying DC function and how these affect IRI. Here, we address current knowledge of the role of DC in regulation of IRI, current gaps in understanding and prospects for innovative therapeutic intervention at the biological and pharmacological levels.